2016
DOI: 10.1016/j.athoracsur.2015.05.107
|View full text |Cite
|
Sign up to set email alerts
|

Benign Metastasizing Leiomyomas to the Lungs: An Institutional Case Series and a Review of the Recent Literature

Abstract: Benign metastasizing leiomyomas are a rare cause of pulmonary nodules. They likely represent a clonal spread of uterine leiomyomas to the lungs. Management includes pathologic diagnosis with long-term surveillance with or without hormonal manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 26 publications
(38 reference statements)
2
94
1
2
Order By: Relevance
“…Benign metastasising leiomyoma is a rare entity with more than 150 cases reported in the www.journals.viamedica.pl literature [3,5]. At least two cases have been also described in the Polish literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign metastasising leiomyoma is a rare entity with more than 150 cases reported in the www.journals.viamedica.pl literature [3,5]. At least two cases have been also described in the Polish literature.…”
Section: Discussionmentioning
confidence: 99%
“…BML occurs mainly in women in reproductive age with a history of surgical treatment for uterine leiomyomas [2,5]. BML foci may be detected from 3 months to even 30 years after hysterectomy or myomectomy [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Shapiro et al reported a case of STUMP tumor with metastasis to the humerus, concluding this group of tumors needs to be under close observation [24]. Kropp et al also diagnosed a uterine STUMP tumor from a primary bone tumor [47,48].…”
Section: Treatment and Post-treatment Follow Upmentioning
confidence: 99%
“…Patients with surgically removed STUMP lesions should get a baseline CT of the chest, abdomen, and pelvis is recommended and then routine physical examinations every 6 months for 5 years and then annually thereafter as recurrences often present as pelvic, abdominal or even as pulmonary metastases [44][45][46][47].…”
Section: Treatment and Post-treatment Follow Upmentioning
confidence: 99%
“…They are considered benign based off their low mitotic activity, lack of anaplasia or necrosis, and limited vascularization [1]. BML were first described in 1939 by Steiner [2]. BML most often occur in the lung, presenting as asymptomatic pulmonary nodules, however they can also be present in the cardiovascular system, lymph nodes, omentum, nervous system and retro-peritoneum and rarely in the spine [3].…”
Section: Introductionmentioning
confidence: 99%